2016
DOI: 10.1371/journal.pone.0161954
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cannabinoid Receptor 2 (CB2) Expression in the Cochlea of Adult Albino Rat and Its Up-Regulation after Cisplatin Treatment

Abstract: We provide evidence for the presence of cannabinoid CB2 receptors in some cellular types of the cochlea of the adult albino rat. Cannabinoids and their receptors are increasingly being studied because of their high potential for clinical use. As a hyperspecialized portion of the peripheral nervous system, study of the expression and function of cannabinoid receptors in the hearing organ is of high interest. Stria vascularis and inner hair cells express CB2 receptor, as well as neurites and cell bodies of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 41 publications
4
27
0
7
Order By: Relevance
“…The underlying mode of action of Cnr2 in any of those cells/tissue remains to be determined. However, both groups demonstrated that Cnr2 expression was up-regulated after Cisplatin exposure [11,12]. This was strengthening an earlier claim for an anti-apoptotic role for Cnr2 in cisplatin-treated cultured cells of an auditory cells line [76].…”
Section: Cnr2 Expression In Physiologically Active and Mature Hcs Ofsupporting
confidence: 80%
See 3 more Smart Citations
“…The underlying mode of action of Cnr2 in any of those cells/tissue remains to be determined. However, both groups demonstrated that Cnr2 expression was up-regulated after Cisplatin exposure [11,12]. This was strengthening an earlier claim for an anti-apoptotic role for Cnr2 in cisplatin-treated cultured cells of an auditory cells line [76].…”
Section: Cnr2 Expression In Physiologically Active and Mature Hcs Ofsupporting
confidence: 80%
“…In the inner ear, a recent report documented spontaneous Cnr2 expression in the cochlear canal of adult rats [11]. Strong immunolabelling of Cnr2 was found in the stria vascularis (SV), and maybe more surprisingly in all inner HCs (IHCs), as well as in the afferent neurites and cell bodies of spiral neurons [11]. All these localizations were confirmed independently, and additional cochlear expression was found in the spiral ligament (SL), the outer HCs (OHCs) and a subset of support cells (SCs), namely the inner and outer pillar cells (IPCs and OPCs respectively) [12].…”
Section: Cnr2 Expression In Physiologically Active and Mature Hcs Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Activation of the type 2 cannabinoid receptor (CB2R) results in decreased leukotriene synthesis and leukocyte migration, as well as a reduction of T-helper 2 (Th2)-cytokine profiles. 9,10 AA is also produced by cleavage of the endocannabinoid and CB2R ligand 2-arachidonoylglycerol (2-AG) by fatty acid amid hydrolase (FAAH) or monoacylglycerol lipase (MAGL), directly increasing the production of inflammatory leukotrienes in AERD. 8,9 In this pilot study, we hypothesized that altered CB2R expression is associated with AERD and represents a novel target for future discovery.…”
mentioning
confidence: 99%